PENGARUH NILAI TUKAR, SUKU BUNGA SBI, INFLASI, DAN PERTUMBUHAN GDP TERHADAP PERGERAKAN IHSG DI BURSA EFEK INDONESIA. - Ika Alivia Rizky; Mohammad Amin; Muhammad Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACT This study was conducted to analyze the effect of the rupiah exchange rate, SBI, Inflation and Gross Domestic on the movement of the composite stock price index on the Indonesia Stock Exchange. The sample in this study is a joint stock price index data for the period 2015-2017. The analytical method used is Multiple Linear Regression with SPSS 22 For Windows Software. based on the results of hypothesis testing that has been done The results of simultaneous testing show that the exchange rate, SBI, inflation and GDP affect the movement of the composite stock price index on the Indonesia Stock Exchange.The partial test results show that the rupiah exchange rate, Bank Indonesia Certificates, Inflation and GDP rates influence the movement of the composite stock price index on the Indonesia Stock Exchange. Keywords: Rupiah Exchange Rate, Bank Indonesia Certificate, Inflation Rate, GDP, and composite stock price index.